Advanced Managerial Accounting Techniques and Decision Support System: An Empirical Analysis of Small And Medium Enterprises in Jordan - Abu Mater, Wesam; Kanasro, H. (European Scientific Journal, ESJ, 2018)
This study investigates the empirical analysis of advanced managerial accounting techniques on decision support system in small and medium enterprises in Jordan. The crucial role played by small and medium-sized companies have a major impact on the economies of countries. Therefore, working at maximum cost-effectiveness is vital to both survival and competitiveness because most SMEs in developing countries operate in crowded and competitive markets. To obtain the objectives of the study, the researcher conducted a questionnaire survey, a sample was of 100 managers and 200 employees’ respondents was purposefully sampled, in SMEs in Amman capital city of Jordan. The purpose of the sample is to see the effect of accounting management techniques and decision support system in small and medium enterprises and the researcher take the demographic variables; gender, management level, age, education, and use of technology and financial controlling systemare taken as moderating variables. The statistical tests were applied to analyze the data. The results of the study showed the significant impact of advanced managerial accounting techniques and decision support on SMEs. The study also found that financial controlling system and the use of technology has a positive impact on performance. In light of the results the researcher has made a number of recommendations that will help the Jordanian enterprises, in order to be able to interact and respond to economic, environmental and social variables and respond to economic, environmental and social variables.